Perancangan sistem informasi manajemen gudang berbasis web pada Cozy Mart - Prandiska, Kelvin; Nataliani, Yessica (IT Explore: Jurnal Penerapan Teknologi Informasi dan Komunikasi, 2025)
PT. Surya Cahaya Kembar or known as Cozy Mart aims to improve the delivery process and inventory management by using a web-based warehouse management information system. Companies have difficulty monitoring stock and distribution accurately as their business grows rapidly. The system analysis and software development method used in this research is Agile, which allows quick adjustments to user needs. The system is designed to include delivery tracking, stock management features and reports to assist staff in making decisions. System design uses Unified Modeling Language (UML) which describes system functionality as a whole. Test results show significant improvements in user satisfaction, as well as the speed and accuracy of warehouse management. PT. Surya Cahaya Kembar (Cozy Mart) hopes to reduce operational errors and optimize business processes by implementing this system. This helps the overall growth of the company.